A Systematic Review of Multi-Component Comprehensive School Physical Activity Program (CSPAP) Interventions. Issue 8 (November 2021) - Pulling Kuhn, Ann; Stoepker, Peter; Dauenhauer, Brian; Carson, Russell L.
Objective: To identify, review, and describe multicomponent physical activity (PA) interventions in terms of: (a) number and combination of Comprehensive School Physical Activity Program (CSPAP) components, (b) study characteristics, and (c) primary outcomes. Data Source: Five electronic databases (i.e., PubMed, PsychInfo, Physical Education Index, Sport Discus, and ERIC). Study Inclusion and Exclusion Criteria: Included articles were peer-reviewed, written in English language, published since 1987, and included multicomponent school-based interventions. Data Extraction: Data items extracted were: school level, setting, CSPAP component description, health outcomes, academic outcomes, main conclusion, and reference. Data Synthesis: Included articles were synthesized by: (1) CSPAP components utilized, and (2) research outcome measured (i.e., health or academic). Results: Across 32 studies, 11 included physical education plus 1 additional CSPAP component (PE + 1); 10 included PE + 2 additional CSPAP components; 8 included PE + 3 additional CSPAP components; and 1 included all 5 CSPAP components. Two other studies included 2 or 3 CSPAP components without PE. Most interventions targeted health outcomes (94%) rather than academic outcomes (6%). Conclusions: Multicomponent approaches aligned with CSPAPs are effective in promoting PA and other positive outcomes for youth in schools. Future research should seek to understand effects of CSPAP components on a variety of outcomes and settings.